The Influence of Project Management Information System, Human Resources Quality and Employee Performance on The Effectiveness of Construction Services at PT. XYZ - Siburian, Kondar Parlindungan; Soekiman, Anton; Pratiwi, A.Andini Radisya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In the construction industry, service effectiveness is greatly influenced by the implementation of project management information systems, the quality of human resources (HR), and employee performance. PT XYZ faces various challenges in project management, such as delays, incompatibility of planning with realization, and lack of an integrated information system to support fast and accurate decision-making. This study aims to analyze the influence of project management information system, human resource quality, and employee performance on the effectiveness of construction services at PT XYZ. The research method used is a quantitative approach with a survey method. Data was collected through a questionnaire involving 86 respondents from various divisions within the company. Data analysis was carried out using the path analysis method to identify direct and indirect relationships between independent variables and bound variables. The results of the study show that the project management information system has a significant effect on employee performance and the effectiveness of construction services. In addition, good quality of human resources contributes to improving the effectiveness of construction services through improving employee performance. The implication of this study is that construction companies need to adopt web-based information systems to improve efficiency in project management. In addition, improving the quality of human resources through employee training and competency development is an important factor in achieving optimal construction service effectiveness.